RANCANG BANGUN SISTEM PENGELOLAAN KEUANGAN MASJID DENGAN METODE PROTOTYPE - Ariana Yunita; Shelma Alifia; Randi Farmana Putra (Journal of Informatics and Computing (RANDOM), 2024)
The mosque is a holy place for Muslims which functions as a place of worship and also various religious activities. In carrying out its functions, there is a mosque administrator called the Mosque Welfare Council (DKM), which is an organization that carries out tasks voluntarily, starting from supervision. maintenance, to financial management. In carrying out financial management, transparency and accountability are important, so this encourages the design of a mosque financial management system. This research uses a case study of the Arrahmah Mosque in Cilegon to assist DKM in carrying out mosque management. So far, financial reports have been stored in one Excel file containing many sheets, where each sheet contains financial reports for a particular month, making it difficult to analyze cash flow. The Ar-Rahmah Mosque's financial reports are distributed by printing and attaching them to the walls of the mosque. This research was conducted to design and build a financial management system for the Ar-Rahmah Mosque that can manage finances and report finances online to mosque congregations using the Prototyping method. The stages begin with requirements gathering, quick design, build prototype, prototype evaluation, implementation design, and testing. The test results show that the Ar-Rahmah Mosque's financial management system can meet all needs and the system can process financial data, assets and activity information which can be accessed via a browser.